PENGARUH TINGKAT SUKU BUNGA, RISIKO PASAR, DEBT.TO.EQUITY RATIO DAN PRICE.EARNING RATIO.TERHADAP RETURN.SAHAM PADA PERUSAHAAN PROPERTI AND.REAL ESTATEDI BURSA EFEK INDONESIA - Rusmala Dewi, Putu Ayu; Panji Sedana, Ida Bagus; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.03.TAHUN 2016, 2016)
Stock return is expected return from an investment that been done by the investor. Without it, investor won’t do any investment. The aim of this research is to recognize the effect of interest rate,market risk, debt to equitypratio and priceparning ratiooto stock return in property and real estate company in Indonesian Stock Exchange. This research conducted on several company that works on Property and Real Estate in Indonesian Stock Exchange within period 2011-2013 with 45 company used as sample. Analysis technique used in this research is multiple linear regression analysis. Result from this research show that Interest Rate SBI have negative effect and no significant to stock return. Market Risk have positive effect and no significant against stock return. Debt topEquity Ratiophave negative effect and no significant to stock return. Price Earning Ratio have positive effect and significant to stock return in property and real estate company in Indonesian Stock Exchange.
Keywords: Return Saham, Suku Bunga SBI, Risiko Pasar, Debt to Equity Ratio, Price Earning Ratio